2019
DOI: 10.1016/j.bandl.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formant proximity and stimulus prototypicality on the neural discrimination of vowels: Evidence from the auditory frequency-following response

Abstract: Cross-language speech perception experiments indicate that for many vowel contrasts, discrimination is easier when the same pair of vowels is presented in one direction compared to the reverse direction. According to one account, these directional asymmetries reflect a universal bias favoring “focal” vowels (i.e., vowels with prominent spectral peaks formed by the convergence of adjacent formants). An alternative account is that such effects reflect an experience-dependent bias favoring prototypical exemplars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Three contrasts showed facilitated and asymmetric discrimination on presenting a less peripheral vowel as standard and a more peripheral vowel as deviant. These results are in line with other behavioral and electrophysiological studies (e.g., Masapollo et al, 2015 , 2017b ; Zhao et al, 2019 ) that also report easier discrimination from a more central to a more peripheral vowel. Only one contrast could be explained within the underspecification approach.…”
Section: General Discussion and Conclusionsupporting
confidence: 92%
“…Three contrasts showed facilitated and asymmetric discrimination on presenting a less peripheral vowel as standard and a more peripheral vowel as deviant. These results are in line with other behavioral and electrophysiological studies (e.g., Masapollo et al, 2015 , 2017b ; Zhao et al, 2019 ) that also report easier discrimination from a more central to a more peripheral vowel. Only one contrast could be explained within the underspecification approach.…”
Section: General Discussion and Conclusionsupporting
confidence: 92%
“…We clearly need further research into the relations between behavioral and neural levels of vowel processing in crosslinguistic studies with adults as well as infants early in development. Several recent ERP studies (Slabu et al, 2012;Zhao et al, 2019) focusing on subcortical auditory processing of speech sounds in adults have found evidence to corroborate some aspects of the existing behavioral data on directional asymmetries (Masapollo et al, 2017a). In the Zhao et al study, English listeners were presented with resynthesized (shortened) versions of the less-focal/English-prototypic /u/ and more-focal/Frenchprototypic /u/ identified by Masapollo et al (2017a) in a passive listening task.…”
Section: Discussionmentioning
confidence: 76%
“…While Zhao et al’s (2019) results revealed an intriguing parallel between subcortical ERP and behavioral measures of auditory vowel processing, the precise nature of the relations between these measures remain unclear in part because they were obtained under very different task demands and stimulus presentation speeds. The behavioral perceptual tasks utilized by Masapollo et al (2017a) and Liu et al (2021) were more demanding in terms of attention and memory than the passive oddball task used by Zhao et al (2019) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The potentially important role of subcortical processes in predicting later language outcomes parallels the significant developmental change in subcortical regions from 7-to 11-months in the whole brain analyses. Indeed, recent growth in the adult research literature has demonstrated repeatedly that early sensory encoding of speech in largely subcortical regions is highly relevant for speech discrimination and highly malleable through experience (Slabu, Grimm, & Escera, 2012;Zhao & Kuhl, 2018;Zhao, Masapollo, Polka, Ménard, & Kuhl, 2019). This result opens many more questions that future research will need to elucidate.…”
Section: Importance Of Complementary Roi and Whole Brain Analysesmentioning
confidence: 99%